Aruna Lama: An Indigenous Identity Beyond the Boundaries - Shrestha, Tara Lal; Shrestha, Bidhya (JODEM: Journal of Language and Literature, 2024)
Aruna Lama, as an indigenous Tamang female singer from Darjeeling, articulates a unique history of struggle in Nepali music. Applying Naila Kabeer’s concept of woman empowerment including insights collected from 10 key informants, this study attempts to answer a key research question: How did Aruna Lama crossover the narrow boundaries and appear as a prominent singer in Nepali music? The findings examine Aruna Lama's life journey and present the aesthetic and ethical essence of her struggle in music history. The conclusions shed light on the ways in which Aruna Lama harnessed her indigenous woman’s identity beyond the boundaries asserting her agency to achieve success.